2022
DOI: 10.3233/wor-205181
|View full text |Cite
|
Sign up to set email alerts
|

Association of stigmatizing attitudes with people’s opinion of depression as a valid reason for sickness absence: A Swedish vignette study

Abstract: BACKGROUND: Depression is a common cause of sickness absence (SA) and also highly associated with stigma. Few studies have addressed the role of stigma in relation to SA. OBJECTIVE: To investigate if attitudes to depression were associated with the public’s opinion of depression as a valid reason of SA. METHODS: The study population (n = 2413) originated from a web-based panel of citizens. The survey included a short vignette describing a person with symptoms of depression and the person’s work tasks, followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…In one survey, 26% of patients with MDD reported experiencing workplace discrimination, more than 50% expected to face discrimination, and 73% concealed their mental diagnosis ( 35 ). Similarly, a survey of the general public found that many do not regard depression as a valid reason for sickness absence ( 36 ). Stigma may also play a part in the workplace response to mental health injuries.…”
Section: Burden and Unmet Needs Around Mental Health In The Workplacementioning
confidence: 99%
“…In one survey, 26% of patients with MDD reported experiencing workplace discrimination, more than 50% expected to face discrimination, and 73% concealed their mental diagnosis ( 35 ). Similarly, a survey of the general public found that many do not regard depression as a valid reason for sickness absence ( 36 ). Stigma may also play a part in the workplace response to mental health injuries.…”
Section: Burden and Unmet Needs Around Mental Health In The Workplacementioning
confidence: 99%